DETERMINANTS OF HEALTH EXPENDITURE FOR ELDERLY PEOPLE IN TURKEY (Third Sector Social Economic Review, 2020)
The purpose of this research is to examine how health expenditure of elderly people in Turkey changes and to determine which variables influence on health expenditure of elderly people in Turkey. Data used are obtained from Household Consumption Expenditure Survey of 2014, produced by Turkish Statistical Institute (TurkStat) was used to estimate the effects of socio-demographic and economic variables on health expenditure of elderly people in Turkey. According to the results, it has been determined that the elderly people are simultaneously taking decisions about on how much they will spend on health in Turkey. Furthermore, total household expenditure is one of the most important variables on the health expenditure of the elderly people in Turkey.
Keywords: Elderly; double hurdle; Box-Cox transformation; Turkey